Students’ Perceptions Towards the Use of Google Classroom in Learning English - Kintan Ika Warsito Putri (English Education Department Slamet Riyadi University Surakarta, 2022)
The research was aimed: 1) to analyze all activities which were carried out in learning English that used Google Classroom in Students of class VIII at a private school in Central Java in 2021/2022 Academic Years; 2) to analyze students’ perception in teaching learning English towards Google Classroom in Students of class VIII at a private school in Central Java in 2021/2022 Academic Years. Method that used in this research was descriptive qualitative method. The sample of the research were 35 students of Eighth Grade. For collecting data technique, the researcher used interview with English teacher and distributed questionnaire to the students via Google form. Then, the researcher used triangulation to validity the data. For analyzed the data, the researcher used some steps: collecting data, reducting data, displaying data, and verficating data. The result of this research showed that there were some activities which were carried out using Google Classroom namely: explaining the learning material by the teacher, giving the assignment by the teacher, discussing about the material and assignment to the teacher, doing the assignment and sending the result of the assignment by the students. The students perception towards the use Google Classroom was varied namely: students can learn anytime and anywhere, Google Classroom helps students to develop their ability in reading and writing English skill and students can accept learning material easily to understand. Keywords: Students’ Perception, Google Classroom, Learning English.